Pemberdayaan Masyarakat Bidang Kesehatan melalui POSYANDU - Atika Riasari (Fakultas Teknik Universitas Cenderawasih, 2023)
The purpose of this study is to determine the factors related to the utilization of posyandu visits. The method used is descriptive qualitative, namely the formulation of the problem that guides research to explore or photograph the social situation that will be examined as a whole, broad and in -depth.1 Research Results That Posyandu for the community is still less understood and important for health. It is recommended that routine toddlers can be made examples of models to mothers who are not routine so that cadres must provide fractures for toddlers who routinely so that mothers of toddlers continue to routinely use posyandu visits, cadres are expected Puskesmas officers, provide health promotion to young mothers who are young to increase mothers' knowledge about the importance of the use of posyandu and comprehensive approaches and provide motivation to mothers under five to routinely visit Posyandu, provide health education through health education to mothers under five.